Non-severe burn injury increases cancer incidence in mice and has long-term impacts on the activation and function of T cells. Issue 1 (29th April 2022) - Barrett, Lucy W; Fear, Vanessa S; Foley, Bree; Audsley, Katherine; Barnes, Samantha; Newnes, Hannah; McDonnell, Alison; Wood, Fiona M; Fear, Mark W; Waithman, Jason
Abstract: Background: Recent evidence suggests that burn patients are at increased risk of hospital admission for infection, mental health conditions, cardiovascular disease and cancer for many years after discharge for the burn injury itself. Burn injury has also been shown to induce sustained immune system dysfunction. This change to immune function may contribute to the increased risk of chronic disease observed. However, the mechanisms that disrupt long-term immune function in response to burn trauma, and their link to long-term morbidity, remain unknown. In this study we investigated changes to immune function after burn injury using a murine model of non-severe injury. Methods: An established mouse model of non-severe burn injury (full thickness burn equivalent to 8% total body surface area) was used in combination with an orthotopic model of B16 melanoma to investigate the link between burns and cancer. Considering that CD8 + T cells are important drivers of effective tumour suppression in this model, we also investigated potential dysregulation of this immune population using mouse models of burn injury in combination with herpes simplex virus infection. Flow cytometry was used to detect and quantify cell populations of interest and changes in immune function. Results: We demonstrate that 4 weeks after a non-severe burn injury, mice were significantly more susceptible to tumour development than controls using an orthotopic model of B16 melanoma. In addition, our results reveal that CD8 + T cell expansion, differentiation and memory potential is significantly impaired at 1 month post-burn. Conclusions: Our data suggests that CD8 + T cell-mediated immunity may be dysfunctional for a sustained period after even non-severe burn injury. Further studies in patients to validate these findings may support clinical intervention to restore or protect immunity in patients after burn injury and reduce the increased risk of secondary morbidities observed. Graphical Abstract: